Two new terpenoids from fruits of Ziziphus jujuba - Guo, S.; Tang, Y.P.; Duan, J.A.; Su, S.L.; Ding, A.W.
One new ceanothane-type triterpene and one new sesquiterpene, together with two known triterpenes were isolated from the fruits of Ziziphus jujuba Mill. (Rhamnaceae). Based on the spectral analyses, the structures of two new compounds were elucidated as a-aldehydo-A(1)-norlup-20(29)-en-27,28-dioic acid (zizyberanal acid)(1), and zizyberanone (2). While the two known triterpenes were identified as zizyberanalic acid (3)and ursolic acid (4).
Keywords: ZIZIPHUS JUJUBA; ZIZYBERANAL ACID; ZIZYBERANONE; TRITERPENE; SESQUITERPENE